2011
DOI: 10.3762/bjoc.7.164
|View full text |Cite
|
Sign up to set email alerts
|

Manganese dioxide mediated one-pot synthesis of methyl 9H-pyrido[3,4-b]indole-1-carboxylate: Concise synthesis of alangiobussinine

Abstract: SummaryThe carboline ring system is an important pharmacophore found in a number of biologically important targets. Development of synthetic routes for the preparation of these compounds is important in order to prepare a range of analogues containing the carboline heterocyclic moiety. A manganese dioxide mediated one-pot method starting with an activated alcohol and consisting of alcohol oxidation, Pictet–Spengler cyclisation, and oxidative aromatisation, offers a convenient process that allows access to β-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Furthermore, MFM 501 has a good yield of 20 to 60% as exemplified by the other similar pyrrolidine compounds previously reported using a one-pot reaction [ 22 ]. Besides giving out good yield of intended compounds, the advantages of one-pot reaction schemes include reduction of the time required to set up the reactions, removal of the need to isolate unstable intermediates, and reduction of the time required for purifications which would lead to lowering the cost of overall reaction and lessening wastage to the environment [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, MFM 501 has a good yield of 20 to 60% as exemplified by the other similar pyrrolidine compounds previously reported using a one-pot reaction [ 22 ]. Besides giving out good yield of intended compounds, the advantages of one-pot reaction schemes include reduction of the time required to set up the reactions, removal of the need to isolate unstable intermediates, and reduction of the time required for purifications which would lead to lowering the cost of overall reaction and lessening wastage to the environment [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, the total synthesis of alangiobussinine was reported by Sutcliffe et al in four steps from tryptamine. Their strategy contains long reaction time and tedious steps with 27% overall yield . Recently, Srivastava et al reported an interesting reaction for the total synthesis of alangiobussinine 91 in two steps with 45% overall yield.…”
Section: Cyclic Imines In Joulliè−ugi Reactionmentioning
confidence: 99%
“…Their strategy contains long reaction time and tedious steps with 27% overall yield. 107 Recently, Srivastava et al reported an interesting reaction for the total synthesis of alangiobussinine 91 in two steps with 45% overall yield. This simple and short approach contains IBX-mediated oxidative JU-3CR, followed by another oxidation reaction (Scheme 24).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our investigations commenced with studies on the directed alkynylation of alangiobussinine ( 2a ), which was prepared in a single step from the known β-carboline-1-methyl ester 1 by activation of the ester moiety using 2-hydroxypyridine under aerobic conditions (eq ). Our preparation of 2a from 1 is an improvement in terms of step count and isolated yield over the previously reported synthesis of this natural product . Applying this 2-hydroxypyridine-mediated amidation method, a variety of other β-carboline amide derivatives were accessed in good yields from the corresponding arylethamines.…”
Section: Resultsmentioning
confidence: 96%